KESIAPSIAGAAN PUSKESMAS GARUDA KECAMATAN MARPOYAN DAMAI PEKANBARU DALAM PENANGGULANGAN DEMAM BERDARAH DENGUE (DBD) - LPPM Al-Insyirah (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2016)
Dengue Haemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus. These diseases often cause Extraordinary Events (KLB) and the transmission is through the bite of Aedes aegypti mosquito. Transmission of the disease is influenced by wet weather conditions that can fertilize and reproduce aedes aegypti mosquito breeding. Data in Pekanbaru city Health Department in 2013 showed that there is an increase in the District Marpoyan Peace dengue cases from the previous year and there was one death due to dengue. Garuda PHC contributed most to the increase in dengue cases in these districts. This study aims to describe the health center preparedness in response to Dengue Hemorrhagic Fever (DHF). Research methods with descriptive case study with qualitative data analysis that was conducted in April-June 2014 the District Puskesmas Garuda Marpoyan Peace. The number of research subjects as much as 5 key informants and 2 informant supporters. Method of collecting data through in-depth interviews, observation and document searches. Measuring instruments used as interview guides and checklists. Analysis of the data with the data triangulation and manual. The results showed that there is still a delay in the response preparedness DHF health centers, delays in reporting cases, not maximal epidemiological investigation of dengue cases in the field, yet coordinated health workers and supporters outside the health sector and the limited availability of the operating budget reduction at the district level. PHC expected increase cross-sector partnerships run Pokjanal dengue activity which is a forum program and cross-sectoral coordination for preparedness dengue cases, improving the system in dengue cases reporting lines so that there is no delay in receiving health centers form S.nol and form KDRS.